Inhibition-induced plasticity in tinnitus patients after repetitive exposure to tailor-made notched music. Issue 5 (May 2015) - Stein, A.; Engell, A.; Junghoefer, M.; Wunderlich, R.; Lau, P.; Wollbrink, A.; Rudack, C.; Pantev, C.
Highlights Reduction in tinnitus related neural activity and subjectively perceived tinnitus loudness was achieved after three days of tailor-made notched music exposure. Auditory stimulation with tailor-made notched music evokes inhibition-induced plasticity in a widespread tinnitus network. Repetitive stimulation with tailor-made notched music results in an accumulation of inhibition-induced plasticity.